Toughened of bismaleimide resin with improved thermal properties using amino-terminated Poly(phthalazinone ether nitrile sulfone)s. (7th October 2020) - Liu, Cheng; Qiao, Yue; Li, Nan; Hu, Fangyuan; Chen, Yousi; Du, Gaize; Wang, Jinyan; Jian, Xigao
Abstract: Bismaleimide resin has poor toughness, limiting its wide application potential. High-performance thermoplastic amino-terminated poly(phthalazinone ether nitrile sulfone)s (PPENS-DA) with different cyano group content, have been prepared and used to toughen blends of 4, 4′-bismaleimidodiphenyl-methane (BDM)/diallyl bisphenol A (DABPA). The rheological properties and curing kinetics for the PPENS-DA/BDM/DABPA blends have been investigated using rotational rheometry and DSC. The mechanical and thermal properties of the cured BMI blends have been studied in detail. The effects of level of loading and the cyano group content of PPENS-DA on the mechanical properties of cured blends have been assessed. The notched impact strength of PPENS-DA/BDM/DABPA blends can be up to 3.98 MPa, which is 65.15% higher than that of the pristine BDM/DABPA blend. Simultaneously, the thermal properties of blends have been improved with T g increasing from 237 °C to 265 °C. Furthermore, an isothermal rheological model was established, and the model curve was verified to be consistent with the experimental value. Graphical abstract: Image 1 Highlights: The amino-terminated poly(phthalazinone ether nitrile sulfone)s (PPENS-DA) was introduced into the BDM/DABPA blend system. The impact toughness of BDM was significantly improved by the participating of PPENS-DA in the crosslinking reaction. The introduction of high-performance thermoplastic PPENS-DA improved the glass transition temperature of BDM/DABPA blend. The isothermal rheological model of PPENS-DA/BDM/DABPA blends was established.